Konservasi Yang Hidup Dalam Ritual: Kajian Etnobiologi Upacara Kede Pada Masyarakat Adat Detupera - Pawe, Maria Serlina; Lura, Maria Magdalena Vannessa; Wae, Veronika P Sinta Mbia (BIOEDUKASI (Jurnal Pendidikan Biologi), 2026)
This  article  discusses  the  “Kede”  traditional  ceremony  as  a  form  of  local  wisdom-based  conservation  that  is  still  preserved  by  the  Detupera  indigenous  community,  Ende  Regency.  Through  an  ethnobiological  approach,  this  research  examines  the  symbolism,  ritual  structure,  and  ecological  values  contained  in  the  traditional  practice.  The  “Kede”  ceremony  reflects  the  spiritual  relationship  between  humans,  ancestors  and  nature,  and  contains  customary  rules  that  support  the  sustainable  preservation  of  natural  resources.  The  results  show  that  the  use  of  local  plants  such  as  leke,  denu,  kela  and  lelu  has  symbolic  meanings  that  strengthen  environmental  conservation  and  biodiversity  preservation.  This  ritual  also  functions  as  an  intergenerational  ecological  education  system  within  the  indigenous  community.  Therefore,  the  “Kede”  ceremony  can  be  a  contextual  conservation  model  that  integrates  cultural  values,  spirituality,  and  ecological  ethics  in  maintaining  the  balance  of  nature.Kata  Kunci:  Konservasi,  Upacara  Adat,  Etnobiologi,  Kearifan  Lokal,  Ritual